Cephalopods Between Science, Art, and Engineering: A Contemporary Synthesis - Nakajima, Ryuta; Shigeno, Shuichi; Zullo, Letizia; De Sio, Fabio; Schmidt, Markus R. (Frontiers in Communication, 2018)
ABSTRACT Cephalopods are outstanding animals. For centuries, they have provided a rich source of inspiration to many aspects of human cultures, from art, history, media and spiritual beliefs to the most exquisite scientific curiosity. Given their high esthetical value and ‘mysteriously’ rich behavioral repertoire they have functioned as boundary objects (or subjects) connecting seemingly distinct thematic fields. Interesting aspects of their being span from the rapid camouflaging ability inspiring contemporary art practices, to their soft and fully muscular body that curiously enough inspired both gastronomy and (soft) robotics. The areas influenced by cephalopods include ancient mythology, art, behavioural science, neuroscience, genomics, camouflage technology and bespoken robotics. Although these might seem far related fields, in this manuscript we want to show how the increasing scientific and popular interest in this heterogeneous class of animals have indeed prompted a high level of integration between scientific, artistic and sub-popular culture. We will present an overview of the birth and life of cephalopod investigations from the traditional study of ethology, neuroscience, and biodiversity to the more recent and emerging field of genomics, material industry and soft robotics. Within this framework, we will attempt to capture the current interest and progress in cephalopod scientific research that lately met both the public interest and the ‘liberal arts’ curiosity.